2006
DOI: 10.1126/science.1133601
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of the Full, Sequence-Dependent Folding Landscape of a Nucleic Acid

Abstract: Nucleic acid hairpins provide a powerful model system for understanding macromolecular folding, with free-energy landscapes that can be readily manipulated by changing the hairpin sequence. The full shapes of energy landscapes for the reversible folding of DNA hairpins under controlled loads exerted by an optical force clamp were obtained by deconvolution from high-resolution, single-molecule trajectories. The locations and heights of the energy barriers for hairpin folding could be tuned by adjusting the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
512
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(546 citation statements)
references
References 20 publications
29
512
0
Order By: Relevance
“…This approach has answered one of the most fundamental questions in nucleic acid structure formation, providing direct evidence for the long-held nucleation model for duplex involving formation of 2-3 base pairs prior to rapid formation of the remainder of the duplex [107]. Further, it has been shown that force unfolding data can be deconstructed into a complete energy landscape [108]. It will be fascinating to see if this approach can be applied to increasingly complex RNAs.…”
Section: Rna: Present and Futurementioning
confidence: 99%
“…This approach has answered one of the most fundamental questions in nucleic acid structure formation, providing direct evidence for the long-held nucleation model for duplex involving formation of 2-3 base pairs prior to rapid formation of the remainder of the duplex [107]. Further, it has been shown that force unfolding data can be deconstructed into a complete energy landscape [108]. It will be fascinating to see if this approach can be applied to increasingly complex RNAs.…”
Section: Rna: Present and Futurementioning
confidence: 99%
“…23,33,34 The number of experimentally determined high resolution RNA structures 30,31,35 continues to increase, enabling us to understand the interactions that stabilize the folded states. Single molecule [36][37][38][39][40][41] and ensemble experiments [42][43][44] using a variety of biophysical methods combined with theoretical techniques 14,34 have led to a conceptual framework for predicting various mechanisms by which RNA molecules fold. In order to make further progress new computational tools are required.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike DNA or RNA hairpins, where forces on the order of 15 pN are necessary to induce mechanical unzipping (10,11), the conformations of HJs could be biased at 0.5 pN or lower. The lever arm effect makes it unlikely that a purely mechanical tool could have probed the force effect on HJ conformations because if the arms are lengthened to magnify the distance change, the force effect will occur at even lower forces.…”
mentioning
confidence: 99%